Injectable Hydrogel versus Plastically Compressed Collagen Scaffold for Central Nervous System Applications - Magdalini Tsintou; Kyriakos Dalamagkas; Alexander Seifalian (International Journal of Biomaterials)
Central Nervous System (CNS) repair has been a challenge, due to limited CNS tissue regenerative capacity. The emerging tools that neural engineering has to offer have opened new pathways towards the discovery of novel therapeutic approaches for CNS disorders. Collagen has been a preferable material for neural tissue engineering due to its similarity to the extracellular matrix, its biocompatibility, and antigenicity. The aim was to compare properties of a plastically compressed collagen hydrogel with the ones of a promising collagen-genipin injectable hydrogel and a collagen-only hydrogel for clinical CNS therapy applications. The focus was demonstrating the effects of genipin cross-linking versus plastic compression methodology on a collagen hydrogel and the impact of each method on clinical translatability. The results showed that injectable collagen-genipin hydrogel is better clinical translation material. Full collagen compression seemed to form extremely stiff hydrogels (up to about 2300 kPa) so, according to our findings, a compression level of up to 75% should be considered for CNS applications, being in line with CNS stiffness. Taking that into consideration, partially compressed collagen 3D hydrogel systems may be a good tunable way to mimic the natural hierarchical model of the human body, potentially facilitating neural repair application.